2017
DOI: 10.1016/j.imlet.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines IL-17 and TNF-α up-regulate PD-L1 expression in human prostate and colon cancer cells

Abstract: Programmed cell death protein 1 (PD-1) acts on PD-1 ligands (PD-L1 and PD-L2) to suppress activation of cytotoxic T lymphocytes. Interleukin-17 (IL-17) and tumor necrosis factor-α (TNF-α) are co-expressed by T helper 17 (TH17) cells in many tumors. The purpose of this study was to test if IL-17 and TNF-α may synergistically induce PD-L1 expression in human prostate cancer LNCaP and human colon cancer HCT116 cell lines. We found that IL-17 did not induce PD-L1 mRNA expression, but up-regulated PD-L1 protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(207 citation statements)
references
References 40 publications
6
198
2
1
Order By: Relevance
“…In addition, IL-17 upregulated PD-L1 protein expression in both cell lines. 20 Although still speculative, TNF>, IL-17, and other cytokines that are dysregulated in obesity constitute possible links with EC expression of PD-L1. A link between obesity and immune evasion by PD-L1-mediated suppression of cytotoxic CD8+ T cells is also of interest in cancers other than EC for which there is epidemiological association with obesity.…”
Section: G00001mentioning
confidence: 99%
“…In addition, IL-17 upregulated PD-L1 protein expression in both cell lines. 20 Although still speculative, TNF>, IL-17, and other cytokines that are dysregulated in obesity constitute possible links with EC expression of PD-L1. A link between obesity and immune evasion by PD-L1-mediated suppression of cytotoxic CD8+ T cells is also of interest in cancers other than EC for which there is epidemiological association with obesity.…”
Section: G00001mentioning
confidence: 99%
“…This postulate is based on the observations that PD-L1 expression in tumor cells is induced by IFN-γ (Cheng et al, 2007; Dondero et al, 2016; Iwai et al, 2002; Muhlbauer et al, 2006), and IFN-γ signaling is dependent on sphingolipid metabolism (Bajwa et al, 2017; Ottenlinger et al, 2016; Seo, Alexander, & Hahm, 2011; Wakita, Nishimura, Tokura, Furukawa, & Takigawa, 1996). Furthermore, Akt- (Abdelhamed, Ogura, Yokoyama, Saiki, & Hayakawa, 2016; Atefi et al, 2014; Dong et al, 2016; Lastwika et al, 2016; Song et al, 2013; Yang et al, 2017; Zhao et al, 2017), NF-kB- (Gowrishankar et al, 2015), and TNFα- (Wang et al, 2017) signaling induce PD-L1 expression, and all of these pathways are regulated by sphingolipid signaling. Therefore, manipulation of tumor immunology using SK inhibitors is an unexplored potential new approach to improved cancer therapy.…”
Section: Sphingosine Kinases As Targets For Anticancer Drugsmentioning
confidence: 99%
“…In general, testosterone is considered as an anti-inflammatory while estrogens are more proinflammatory, but several studies show shared effects on immune cells between hormones (indicated in red). References not cited in text: androgens on T helper cells (Sutherland et al 2005, Hepworth et al 2010, Fijak et al 2011, Andersson et al 2015, Wang et al 2017b) and on DCs (Koh et al 2009, Corrales et al 2012; estrogens on T helper cells (Correale et al 1998, Maret et al 2003, Lélu et al 2011, Morse & McNeel 2012, Chen et al 2015 and on DCs (Zhang et al 2004 linked to patient outcomes (Ylitalo et al 2016, Strömvall et al 2017, emphasizing the importance of understanding this biology. The receptor and non-receptor-mediated effects of steroids on innate immune cells have been widely studied in experimental animal models as well as in clinical studies of many diseases (Trigunaite et al 2015, Roved et al 2017.…”
Section: Sex Steroids and The Immune Tumor Microenvironment Effect Ofmentioning
confidence: 99%